Analisis Pengaruh Motivasi Kerja terhadap Kinerja Karyawan Gen Z di Coffee Shop melalui Work-Life Balance di Kota Pontianak - Elis; Octora, Sandra Endang Suci (SAFE-Network, 2025)
This research aims to understand the analysis of work motivation on the performance of Generation Z in coffee shops in Pontianak City, with Work-Life Balance as a mediator. This research uses a quantitative model and processes data through PLS-SEM. It is proven that motivation contributes to performance or high motivation will increase performance. Life balance contributes and mediates the relationship between motivation contributes to performance directly or through Work-Life Balance. Therefore, the mediating variable plays a major role in strengthening the influence of motivation on the performance of Generation Z employees. This research has implications for coffee shop management to pay attention to the Work-Life Balance of their employees to develop their motivation and performance in a comprehensive manner.